2022
DOI: 10.3390/jof8060613
|View full text |Cite
|
Sign up to set email alerts
|

Four New Species of Harringtonia: Unravelling the Laurel Wilt Fungal Genus

Abstract: Symbiosis between beetles and fungi arose multiple times during the evolution of both organisms. Some of the most biologically diverse and economically important are mutualisms in which the beetles cultivate and feed on fungi. Among these are bark beetles and Harringtonia, a fungal genus that produces Raffaelea-like asexual morph and hosts the causal agent of laurel wilt, H. lauricola (formerly Raffaelea lauricola). In this study, we propose four new species of Harringtonia associated with beetles from Belize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Modern ambrosia research has continued to reveal the varied range of relationships shared between xyleborine ambrosia beetles and fungi (Kostovcik et al 2015, Skelton et al 2018. This includes the identification of many previously unknown fungal symbionts (von Arx and Hennebert 1965;Harrington et al 2008Harrington et al , 2014Freeman et al 2013;Li et al 2016;Lynch et al 2016;Simmons et al 2016aSimmons et al , 2016bAoki et al 2018Aoki et al , 20192021;Lynn et al 2020;Mayers et al 2020aMayers et al , 2020bAraújo et al 2022) and recognition that the same species of ambrosia fungus might grow in the galleries of non-xyleborine beetles as well as those of xyleborines (Gebhardt et al 2004). Since the discovery and identification of the mycangium (Francke-Grosmann 1956, Schedl 1962, Batra 1963, research has revealed the central role this organ plays in the development and maintenance of ambrosia symbioses (Mayers et al 2022).…”
Section: History Of Research Regarding Ambrosia Fungimentioning
confidence: 99%
See 4 more Smart Citations
“…Modern ambrosia research has continued to reveal the varied range of relationships shared between xyleborine ambrosia beetles and fungi (Kostovcik et al 2015, Skelton et al 2018. This includes the identification of many previously unknown fungal symbionts (von Arx and Hennebert 1965;Harrington et al 2008Harrington et al , 2014Freeman et al 2013;Li et al 2016;Lynch et al 2016;Simmons et al 2016aSimmons et al , 2016bAoki et al 2018Aoki et al , 20192021;Lynn et al 2020;Mayers et al 2020aMayers et al , 2020bAraújo et al 2022) and recognition that the same species of ambrosia fungus might grow in the galleries of non-xyleborine beetles as well as those of xyleborines (Gebhardt et al 2004). Since the discovery and identification of the mycangium (Francke-Grosmann 1956, Schedl 1962, Batra 1963, research has revealed the central role this organ plays in the development and maintenance of ambrosia symbioses (Mayers et al 2022).…”
Section: History Of Research Regarding Ambrosia Fungimentioning
confidence: 99%
“…De Beer et al ( 2022) recently described the new genus Harringtonia to accommodate three former Raffaelea species: Raffaelea aguacate Simmons, Dreaden and, Ploetz, Raffaelea brunnea Batra (associated with Corthylini ambrosia beetles), and Raffaelea lauricola Harrington Fraedrich and Aghayeva, the causal agent of laurel wilt (Fraedrich et al 2008. Only H. lauricola is a pathogen, while other Harringtonia species appear harmless (Araújo et al 2022). Harringtonia ambrosioides Araújo, Li, and Hulcr was recently described after being isolated from the Neotropical xyleborine Dryocoetoides capucinus (Eichhoff) (Araújo et al 2022).…”
Section: Xyleborus Glabratus-harringtonia Lauricolamentioning
confidence: 99%
See 3 more Smart Citations